2022
DOI: 10.1080/14756366.2022.2116015
|View full text |Cite
|
Sign up to set email alerts
|

Rational design, synthesis, and pharmacological characterisation of dicarbonyl curcuminoid analogues with improved stability against lung cancer via ROS and ER stress mediated cell apoptosis and pyroptosis

Abstract: Curcumin is a natural medicine with a wide range of anti-tumour activities. However, due to β-diketone moiety, curcumin exhibits poor stability and pharmacokinetics which significantly limits its clinical applications. In this article, two types of dicarbonyl curcumin analogues with improved stability were designed through the calculation of molecular stability by density functional theory. Twenty compounds were synthesised, and their anti-tumour activity was screened. A plurality of analogues had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…195 °C–196 °C. 18,19 Reactions of the bis-chalcone 6 with Reagents 7 – 9 gave the target Compounds 1 – 3 in good yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…195 °C–196 °C. 18,19 Reactions of the bis-chalcone 6 with Reagents 7 – 9 gave the target Compounds 1 – 3 in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…195 °C-196 °C. 18,19 Reactions of the bis-chalcone 6 with Reagents 7-9 gave the target Compounds 1-3 in good yields. The structure of Compound 1 was confirmed by the presence of the amide carbonyl stretching vibration at 1660 cm −1 in its infrared (IR) spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of institutions, Wenzhou Medical University was the institution that published the most researches on curcumin and tumor in the world. In their latest researches, they designed two dicarbonyl curcumin analogues with improved stability, and screened their anti-tumor activities, showing excellent in vivo and in vitro lung cancer activity ( 25 ). We analyzed the most influential authors, and the results showed that Aggarwal BB and Banerjee s were the authors with the largest number of curcumin and tumor related publications, 20 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBP-homologous protein (CHOP) and glucose-regulated protein 78 (GPR78) are key markers of ER stress, and their upregulation indicates that cells suffer from different levels of ER stress ( 18 ). It has been shown that lung cancer cell death is caused by ER stress, which may be due to ER stress-mediated apoptosis ( 19 ). In addition, it has also been found that lead-induced nephrotoxicity is mainly due to apoptosis, which is closely associated with ER stress ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…ER stress can activate the Nrf2 signaling pathway through protein kinase RNA-like ER kinase (PERK) ( 22 , 23 ). It has been shown that curcumin can effectively upregulate the level of reactive oxygen species in lung cancer cells, which in turn activates ER stress, leading to apoptosis and cell scorching ( 19 ).…”
Section: Introductionmentioning
confidence: 99%